Femoroacetabular impingement: biomechanical and dynamic considerations - Dall'Oca, C.; Maluta, T.; Micheloni, G. M.; Romeo, T.; Zambito, A.; Malagò, R.; Magnam, B. (Acta Biomedica Atenei Parmensis, 2014)
Femoroacetabular impingement (F.A.I.) is a pathologic process caused by an abnormal shape of the acetabulum, of the femoral head, or both. F.A.I., often referred to as idiopathic, may be secondary to slipped capital femoral epiphysis, congenital hypoplasia of the femur, Legg-Calvé Perthes disease, post-traumatic mal-union and protrusio acetabuli. From 2009 to 2012 we studied 21 patients (14 males), with a mean age of 52 (33 y - 75 y), affected by idiopathic F.A.I. Every patient underwent pelvic and hip joint X-rays and CT scan with 3D reconstructions, in order to evaluate the morphology of the pelvis and the hip joint and the torsion of the lower limbs (Femoroacetabular ante-retroversion). Our results show an average femoral ante-version angle of 12,4° (15°-20° physiological range) in patients affected by CAM impingement and an average acetabular ante-version angle of 13,5° (15°-20° physiological range) for those with PINCER impingement. These values, in patients affected by F.A.I., are probably related to morphologic and biomechanical features that may lead to the onset of idiopathic femoroacetabular impingement. In the literature, other studies partially support our findings, suggesting a more critical approach to a patient with idiopathic F.A.I. extending evaluations to nearby articulations.